Enhancing students’ motivation with Kahoot!: a case study in English and mathematics - Pais, S. (2021)
In the last few decades, technology has advanced in multiple fields, including Education. Some of its benefits include improving student performance and motivation, fostering active learning and tracking student progress. As a "new learning generation" is around, profound changes to the role and function of both teachers and students are particularly vital, so active, cooperative and participative methodologies of learning must be privileged. Given that most higher education students are technology savvy and very receptive to the integration of Web 2.0 tools in class, the teachers involved in this study began using Kahoot! in their classes as an alternative teaching methodology. The participants in the study are undergraduate students from a Portuguese higher education institution and encompassed the curricular units of Statistical Analysis and English. The aim of the study is to investigate students’ perceptions of how Kahoot! can be used as a tool for testing new vocabulary, reviewing class content or designing warm-up activities. A quantitative survey is being conducted to gather information about students’ insights on the use of Kahoot!. Similar studies have shown that students are generally receptive to the use of this tool and find it useful to increase their motivation.